UI/UX Design in E-Learning University of Harapan Medan using User Centered Design (UCD) - Haliz Larasati; Edy Rahman Syahputra; Edrian Hadinata (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2022)
The development of information technology that is used as a learning medium in the form of e-learning (Electronic Learning) has become an educational system that is quite important and is often used today. University of Harapan Medan uses e-learning as a learning medium, but it has not been fully utilized. Therefore, e-learning requires an updated and developed user interface design to improve the user experience. The system design uses the User-Centered Design (UCD) method, which focuses on the user as the center of each design process. The approach with this method can provide advice on interface design on an e-learning website as a solution according to user needs